Procedures Used in the Translation of Culture Specific Items in Moroccan Literary Texts: Lu’bat al-Nisyan as a Case Study - chibani, ikrame (International Journal of Language and Literary Studies, 2022)
In recent times, literary translation seems to have gained considerable interest among translation scholars and translators. Furthermore, translating culture-specific items (CSIs) in literary texts appear to be one of the most challenging tasks a translator must overcome. In the present article, attempts were made to describe the most and least frequent translation procedures adopted by translators to overcome cultural barriers in the translation of the literary text. The current study used Newmark’s model (1988) for cultural translation, which includes cultural categories and translation procedures to classify the data. Through this model, it was concluded that in the case studied, ‘The Game of Forgetting’, the translator used most frequently modulation, functional equivalent and cultural equivalent to render the meaning of the source text, such as expansion and notes were barely used.